AN EXPERIMENTAL STUDY FOR DAMAGE CHARACTERIZATION OF POLYURETHANE STEEL SANDWICH PLATE UNDER MODE-I LOADING - Siswanti, Heni; Zubaydi, Achmad; Piscesa, Bambang; Syahab, Husein; Ariesta, Rizky Chandra (Journal of Applied Engineering Science, 2025)
An experimental study is presented to characterize the face or core debonding on sandwich plate specimens under mode-I loading. The experiment was conducted with the specimens of an asymmetrical double cantilever beam (ADCB). Several specimens with different core thicknesses were analysed to estimate the strain energy release rate (SERR). The SERR of mode-I (GI) calculation uses two data reduction methods namely the Modified Beam Theory (MBT) and Compliance Calibration (CC) methods. The GI depicted on the R-Curve expresses the damage behaviour of the sandwich plates. The critical energy release rate (GIC) resulted of the MBT data reduction method produces a higher value than CC method, due to the differing assumptions between the two methods. The GIC value also correlates directly with the peak load value. The difference in sandwich plate thickness, particularly the core material thickness, does not significantly affect the damage behavior regarding the sandwich material's GIC value.
Keywords: sandwich, experiment, mode-i, energy release rate, debonding